2022
DOI: 10.3855/jidc.16058
|View full text |Cite
|
Sign up to set email alerts
|

MRSA as an indicator of infection control measures in Turaif General Hospital, Northern Area-Saudi Arabia

Abstract: Introduction: Saudi Arabia can be considered a hot spot for Methicillin-resistant Staphylococcus aureus (MRSA) infections with significant regional variations. As far as we know, this is the first study to evaluate the prevalence of MRSA in clinical samples obtained from Turaif general hospital (TGH), Northern Area-Saudi Arabia, and screening the resistance profile to the most regularly used antimicrobials as an indicator for evaluation of the implemented infection control measures. Methodology: Totally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Additionally, a retrospective study by Farah et al at a major medical city in Riyadh revealed a 17.5 % MRSA prevalence from 2010 to 2015 ( Farah et al, 2019 ). Furthermore, Taha et al found a 39 % MRSA prevalence in a 6-month cross-sectional study in the Northern region ( Taha et al, 2022 ). Locally, Alaklobi and colleagues found that the prevalence of MRSA was 23.3 % among outpatient children in Riyadh Saudi Arabia ( Alaklobi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a retrospective study by Farah et al at a major medical city in Riyadh revealed a 17.5 % MRSA prevalence from 2010 to 2015 ( Farah et al, 2019 ). Furthermore, Taha et al found a 39 % MRSA prevalence in a 6-month cross-sectional study in the Northern region ( Taha et al, 2022 ). Locally, Alaklobi and colleagues found that the prevalence of MRSA was 23.3 % among outpatient children in Riyadh Saudi Arabia ( Alaklobi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the literature was searched for surveillance studies involving MRSA in Saudi Arabia, 17 studies were found [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The number of reported isolates ranged from 4 to 4853 MRSA isolates [ 25 , 26 , 28 , 29 , 30 , 31 , 32 , 33 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resistant Gram-positive Pathogensmentioning
confidence: 99%
“…When the literature was searched for surveillance studies involving MRSA in Saudi Arabia, 17 studies were found [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The number of reported isolates ranged from 4 to 4853 MRSA isolates [ 25 , 26 , 28 , 29 , 30 , 31 , 32 , 33 , 37 , 38 , 39 , 40 , 41 ]. The average prevalence of MRSA among all S. aureus isolates in the studies that reported it was 32.5% [ 26 , 28 , 31 , 32 , 36 , 38 , 41 ], while the prevalence of S. aureus among total Gram-positive bacteria was about 24.8% [ 29 , 31 ].…”
Section: Resistant Gram-positive Pathogensmentioning
confidence: 99%
See 2 more Smart Citations